[Marcos ; Street children ; John Lesaca [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
Taking a look at the hidden wealth of Marcos and what may happen in the event of his death. A story about Victor, a victim of child abuse, whon ran away from home and now lives in Manila streets. A jazz violinist who mixes the classical with the contemporary sound.